Citizenship Education Model For The Establishment Of Legal Awareness To Implement The Social Functions Of Land Rights - Rejekiningsih, Triana (Sebelas Maret University, 2016)
This study aims to explore: (1) The importance of citizenship education to shape of legal awareness ofcitizensâ; (2) the essence of the implementation of the principle of the social function of land rights; and (3)Â Competence citizensâ awareness applying the principle of the social function of land rights. This study usedÂ a qualitative approach, the method of socio legal research, by looking at the effectiveness of the law inÂ society. Data analysis techniques in this study conducted with interactive analysis of data items, namely theÂ data collection, data reduction, the data presentation and conclusion. Conclusions The results were obtained:Â (1) Civics is very important to establish the legal awareness of citizensâ, who can participate and beÂ responsible for applying the law, to achieve the greatest prosperity of the people; (2) The essence of theÂ application of the principle of the social function of land rights be realized through the use of land that doesÂ not harm the public interest, land tenure the which does not exceed the maximum limit of land ownership,Â working on their own land with the characteristics of the soil, preventing the ways extortion and maintainÂ the land, including adding and prevent damage fertility; and (3) Competence citizensâ awareness applyingÂ the principle of the social function of land rights consist of legal knowledge of citizensâ against the principalÂ of social function of land rights, the attitude of citizens to comply with the rights and obligations of land,Â and establish skills of citizens in harnessing and using the land, as living resources together to achieve theÂ greatest prosperity of the people